Distinctive signs as an alternative for the revitalization of the productive system of ocañera onion (Allium cepa L.): An analysis of scientific trends - Flórez-Martínez, Diego Hernando (2025)
The current context of agribusiness is framed by three major drivers: business models based on bioeconomy and circular economy; mechanisms that ensure quality, safety, and traceability throughout the supply chain; and aspects of the Trade-Related Intellectual Property Rights (TRIPS) agreement. The latter has become a differential factor for both comparative and competitive advantage and is recognized as a potential enabler or constraint for the positioning of primary, minimally processed, and transformed agricultural products. In the case of Ocañera red onion as a primary product, access to distinctive signs covered by the TRIPS agreement, such as denomination of origin or geographical indication, would benefit the promotion of its cultivation, protect trade against homologous varieties from neighboring countries introduced without restriction, and facilitate the promotion of characteristics related to its bioactive and functional components beyond organoleptic properties. For this research, a methodological design based on mixed methods of scientometrics, systematic literature review, and qualitative meta-analysis was implemented, aimed at identifying research trends in distinctive signs for primary agricultural products. From these trends and focusing on specific information about vegetables, enabling and restrictive factors related to distinctive signs were identified. These factors were used to analyze homologous cases of distinctive signs reported for primary agricultural products of the Allium genus. Finally, key factors were classified into five categories related to regulations, product added value characteristics, territory specificities, available technologies for origin and quality assessment, and market dynamics and merged in a five-step route to undertake a certification process for distinctive signs for Ocañera red onion.